2021
DOI: 10.24018/ejedu.2021.2.5.147
|View full text |Cite
|
Sign up to set email alerts
|

Sports Betting Among Students of Colleges of Education in the Ashanti Region of Ghana

Abstract: Sports betting has recently become prevalent among students in institution of higher learning. Most students spend substantial amount of their time engaging in sports betting. The purpose of the study was to examine sports betting among students at colleges of education in the Ashanti Region of Ghana. The descriptive survey design was used for the study. The target population was students in colleges of education in the Ashanti Region of Ghana. The simple random sampling procedure was employed to select 361 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Easy access to internet is a big problem challenging mostly the adolescent as parents provide it for the children not minding the negative implication. The findings of this study is in support of Opoku and Yeboah [8] who found out that students engage in sport betting because to win cash and for entertainment. Most often, students engage into football because they are already very use to the activities, they cannot concentrate without placing bet.…”
Section: Discussion Of Findingssupporting
confidence: 88%
See 1 more Smart Citation
“…Easy access to internet is a big problem challenging mostly the adolescent as parents provide it for the children not minding the negative implication. The findings of this study is in support of Opoku and Yeboah [8] who found out that students engage in sport betting because to win cash and for entertainment. Most often, students engage into football because they are already very use to the activities, they cannot concentrate without placing bet.…”
Section: Discussion Of Findingssupporting
confidence: 88%
“…The effect of the above behaviour is detrimental as it incubates poverty, frustration, laziness, waste of resources, illusions, fantasy, wrong ideas about wealth, lack of vision and creativity. Emmanuel and Terdoo, [8] conclude in their findings that the prevalence of betting is on a high side because the motivation is mainly on financial empowerment. Opoku and Yeboah [9] also indicated that students engage in sport betting because of cash winning and entertainment.…”
Section: Original Research Articlementioning
confidence: 98%
“…Currently, it is a growing public health concern globally [2][3][4]. The advent of internet gambling and easy access to mobile phones and televisions have made gambling easy [5], with more youth of the working age group getting involved [5][6][7][8][9]. It is legal to engage in online sports betting in Ghana according to the Gaming Act of 2006.…”
Section: Introductionmentioning
confidence: 99%